2019
DOI: 10.3892/ol.2019.10078
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated forkhead‑box A3 elevates the expression of forkhead‑box A1 and forkhead‑box A2 to promote metastasis in esophageal cancer

Abstract: Esophageal cancer (EC) is one of the most lethal cancers currently known. Members of the forkhead-box A (FOXA) family, including FOXA1 and FOXA2, have been reported to regulate EC progression. However, the role of FOXA3, which is another FOXA member, has not yet been investigated. In the present study, public dataset analyses and immunohistochemistry of 96 samples from patients with EC were performed to determine the potential roles of FOXA3 in EC. The results revealed that FOXA3 was significantly upregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…High expression of FoxA3 was correlated with poor prognosis in lung cancer [16]. FoxA3 was also up-regulated and promoted metastasis in esophageal cancer cells through the regulations of FoxA1 and FoxA2 expressions [17]. These suggested that FoxA3 plays oncogenic function in lung cancer and esophageal cancer via elevation of FoxA1 and FoxA2 expressions.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…High expression of FoxA3 was correlated with poor prognosis in lung cancer [16]. FoxA3 was also up-regulated and promoted metastasis in esophageal cancer cells through the regulations of FoxA1 and FoxA2 expressions [17]. These suggested that FoxA3 plays oncogenic function in lung cancer and esophageal cancer via elevation of FoxA1 and FoxA2 expressions.…”
Section: Discussionmentioning
confidence: 85%
“…High expressions of FoxA1 and FoxA3 in lung cancer were related with poor overall survival, whereas FoxA2 overexpression was associated with a better overall survival, suggesting the opposing roles between FoxA1/A3 and FoxA2 in the carcinogenesis [16]. FoxA1, FoxA2 and FoxA3 play synergistic roles in metastasis of esophageal cancer [17]. Expressions of estrogen receptors and EMT markers are induced along with CCA progression [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, it was observed that FOXA2 was highly expressed in ESCC and its high expression was associated with TNM stage, distant metastasis, and relapse. In addition, FOXA2 was upregulated in esophageal adenocarcinoma and worked as a potential indicator in the tumor development [ 17 , 27 , 28 ]. These results were consistent with our findings that FOXA2 knockdown suppressed ESCC proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, sparse data is available on the role of FoxA3 in cancer. One recent study demonstrated an increase in FoxA3 expression in esophageal cancer, which was associated with increased invasion, distant metastasis, disease stage, and a shorter overall survival ( 38 ). However, these TFs are correlated with oncogenic but also conversely tumor-suppressive functions (inhibiting metastasis) depending on how they interact with the transcriptional networks of tissue-specific cancers ( 29 , 39 , 40 ).…”
Section: Forkhead Box Amentioning
confidence: 99%